Strategi Komunikasi Dakwah Digital dalam Meningkatkan Literasi Keagamaan Generasi Z - Sarmila Sarmila; Lukman Nurchakim; Susanti Susanti; Renal Saputra (Khulasah : Islamic Studies Journal, 2026)
This study aims to analyze digital da'wah communication strategies in improving the religious literacy of Generation Z amid the rapid development of information technology. The research employed a qualitative approach using the library research method. Data were collected from various academic sources, including scientific journals, books, conference proceedings, and previous studies relevant to da'wah communication, digital media, religious literacy, and the characteristics of Generation Z. Data analysis was conducted using content analysis techniques through the stages of data reduction, data classification, data presentation, and conclusion drawing. The findings indicate that digital media platforms such as Instagram, TikTok, and YouTube serve as effective tools for delivering Islamic messages to Generation Z. Effective digital da'wah communication strategies include the use of engaging visual and audiovisual content, communicative language, interactive features, and the presentation of materials relevant to the needs of young people. Digital da'wah not only expands access to religious knowledge but also enhances Generation Z's ability to understand, select, and critically evaluate religious information. Therefore, digital da'wah plays an important role in strengthening the religious literacy of Generation Z in the digital era.